Visualisasi Nalar Esoteris dalam Tafsir Melayu-Jawi (Studi Interpretasi QS. Al-Fatihah dalam Manuskrip Tafsir M. Basiuni Imran Sambas Dan Tafsir Nurul Ihsan Said bin Umar Al-Kedah) - Wendi Parwanto; Riyani Riyani (UIN Sunan Kalijaga Yogyakarta, 2022)
Research on M. Basiuni Imran and Said b. Umar Al-Kedah has been carried out by many researchers, including Luqman, who studies the description of the interpretation SevenSurah by M. Basiuni Imran, M. Nazri, examines the application of qiraat in the interpretation of Nurul Ihsan, and several other researchers.Thus in general, the research that has been done is conceptual in nature, has not studied the esoteric aspects in the interpretation of M. Basiuni Imran and Said b. Umar al-Kedah. Based on these reasons, this research is important to be conducted.This articleislibrary research and usesthe theory of power relation and actor-network. The conclusions of this article are: First, the Esoteric Interpretation of Qs. Al-Fatihah; Said b. Umar and Basiuni Imran both interpreted literal-textualism, then later interpreted esoteric-theosophical interpretations. Second, the Meaning of Qs Interpretation. Al-Fatihah; Basiuni Imran understands and interprets that in general-textual Qs. al-Fatihah contains an esoteric meaning, while Said b. Umar understands and interprets parochially that only a few verses in Qs. Al-Fatihah has an esoteric dimension. Third, the Emergence of Esoteric Interpretation Visualization in Qs. Al-Fatihah: 1) Intellectual relations between teachers and students which are the basis for regulation and normalization of interpreters' thoughts; 2) The historical and anthropic-social that developed before and when the commentary was written, and 3) The relations and tendencies of Sufism or tarekat literature that develop in the reality of society so that they hegemony and form the esoteric interpretation of M. Basini Imran and Said b. Umar.